The Development of a Learning Management Model for the Product Exhibition Subject (Course Code 20202-2007) Through Active Learning Process and Teaching Materials for 3rd Year Vocational Certificate Students in Marketing at Nakhon Pathom Municipal Vocational College - Jaiborisut, Titiwarada (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
Abstract ​This research It is research and development. (Research and Development) The objectives are to 1) study basic information and needs for developing a learning management model. 2) create and find basic quality of a learning management model for subjects, product exhibitions. 3) Experiment with the learning management model and 4) Evaluate and improve the learning management model. ​The results of this research were as follows: ​1. The Results of the study of basic information and needs for developing a learning management model. of the students concluded that Organizing learning about product exhibitions Using the learning process Active learning together with teaching documents Appropriate and consistent with teaching and learning arrangements ( =4.60, S.D. = 0.45) ​2. The results of creating and determining the preliminary quality of the learning management model found that the learning management model has important elements: (1) a learning management plan Using the learning process Active Learning There are 4 steps: the introduction step The efficiency (E1/E2) of the learning management model is equal to 84.24/87.69, in line with the specified standard criteria. into the lesson group work steps Application steps Summary and evaluation stage (2) teaching documents Overall consistency is at the highest level. ​3. The results of the experiment found that academic achievement in product exhibition subjects After studying with the learning management model Using the learning process Active learning together with teaching documents Scores equal to or greater than 80 percent with statistical significance at the .05 level and students are satisfied with the teaching and learning arrangements are at a high level. ( = 2.59, S.D.= 0.21) ​4.Evaluation and improvement found that efficiency (E1/E2) of learning management formats, subjects, product exhibitions Using the learning process Active learning together with teaching documents From the experiment with the sample group, the value is equal to 85.22/91.50 Effective according to the specified standard criteria and opinions of students regarding the overall learning management model. Percentage of students 90.00 Agree with the learning management model